Molecular dissection of membrane-transport proteins: mass spectrometry and sequence determination of the galactose-H+ symport protein, GalP, of Escherichia coli and quantitative assay of the incorporation of [ring-2-13C]histidine and (15)NH(3). - Venter, Henrietta (2002)
The molecular mass of the galactose-H(+) symport protein GalP, as its histidine-tagged derivative GalP(His)(6), has been determined by electrospray MS (ESI-MS) with an error of <0.02%. One methionine residue, predicted to be present from the DNA sequence, was deduced to be absent. This is a significant advance on the estimation of the molecular masses of membrane-transport proteins by SDS/PAGE, where there is a consistent under-estimation of the true molecular mass due to anomalous electrophoretic migration. Addition of a size-exclusion chromatography step after Ni(2+)-nitrilotriacetate affinity purification was essential to obtain GalP(His)(6) suitable for ESI-MS. Controlled trypsin, trypsin+chymotrypsin and CNBr digestion of the protein yielded peptide fragments suitable for ESI-MS and tandem MS analysis, and accurate mass determination of the derived fragments resulted in identification of 82% of the GalP(His)(6) protein. Tandem MS analysis of selected peptides then afforded 49% of the actual amino acid sequence of the protein; the absence of the N-terminal methionine was confirmed. Matrix-assisted laser-desorption ionization MS allowed identification of one peptide that was not detected by ESI-MS. All the protein/peptide mass and sequence determinations were in accord with the predictions of amino acid sequence deduced from the DNA sequence of the galP gene. [ring-2-(13)C]Histidine was incorporated into GalP(His)(6) in vivo, and ESI-MS analysis enabled the measurement of a high (80%) and specific incorporation of label into the histidine residues in the protein. MS could also be used to confirm the labelling of the protein by (15)NH(3) (93% enrichment) and [(19)F]tryptophan (83% enrichment). Such MS measurements will serve in the future analysis of the structures of membrane-transport proteins by NMR, and of their topology by indirect techniques.